ANALISIS PENGARUH PEMASARAN RELASIONAL TERHADAP KEPUASAN NASABAH DALAM MEMILIH PRODUK PERBANKAN (STUDI KASUS PADA NASABAH PRIORITAS BANK-BANK BUMN DI BANJARMASIN). - Kristin Meilisa; Marijati Sangen (JWM (JURNAL WAWASAN MANAJEMEN), 2018)
This study aims to identify and analyze the influence of relationship marketing in the form of understanding customer expectations, building service partnership and trust simultaneously and partially to customer satisfaction on choosing banking products, a case study of priority customers on public Banks in Banjarmasin. The study was conducted by using multiple linear regression analysis to find the influence of the independent variable (X) to the dependent variable (Y), simultaneously and partially. The results showed that simultaneously relationship marketing variables significantly influenced customer. Partially, understanding customer expectations has no significant effects to customer satisfaction. Building service partnership and trust significanly influence customer satisfaction and trust is a dominant variable in achieving customer satisfaction. Public Bank in Banjarmasin should be able to increase trust its customers with all efforts.